Universal quantum control of two-electron spin quantum bits using dynamic nuclear polarization - Foletti, Sandra; Bluhm, Hendrik; Mahalu, Diana; Umansky, Vladimir; Yacoby, Amir (Nature physics, 2009)
One fundamental requirement for quantum computation is to carry out universal manipulations of quantum bits at rates much faster than the qubit’s rate of decoherence. Recently, fast gate operations have been demonstrated in logical spin qubits composed of two electron spins where the rapid exchange of the two electrons permits electrically controllable rotations around one axis of the qubit. However, universal control of the qubit requires arbitrary rotations around at least two axes. Here, we show that by subjecting each electron spin to a magnetic field of different magnitude, we achieve full quantum control of the two-electron logical spin qubit with nanosecond operation times. Using a single device, a magnetic-field gradient of several hundred millitesla is generated and sustained using dynamic nuclear polarization of the underlying Ga and As nuclei. Universal control of the two-electron qubit is then demonstrated using quantum state tomography. The presented technique provides the basis for single- and potentially multiple-qubit operations with gate times that approach the threshold required for quantum error correction. The spin state of two electrons in a double well is a promising qubit. Now, such qubits can be arbitrarily rotated around two different axes by applying a magnetic field of different magnitude to each electron. This can be done in nanoseconds, before the stored information is lost.